O efeito do sombreamento e diodos de bypass em módulos fotovoltaicos - Coutinho, Carlos Roberto (2016)
This paper discusses the effects caused in the microgeneration systems due to shading of photovoltaic modules. Although the photovoltaic systems are an alternative for electricity generation, must noted the interference caused by the installation nearby structures. These structures can cause shadow regions, affecting the yield of the photovoltaic system. The mode how the solar cells are interconnected can generate malfunction of some photovoltaic modules, thus reducing the power generated by the system, even with few cells shaded. Through an electronic circuit that varies the load applied in the photovoltaic module and collects data, as voltage and electric current, the characteristic curves of photovoltaic modules with different levels of shading are drawn. These curves are used in the comparison among the different levels, in the verification of the effects caused by shading, and how bypass diodes can mitigate these effects. At the end, through a photovoltaic module having two possible configurations for the connection of bypass diodes, this study analyzes the system under a shading condition, using both configurations.